An Examination of the Structural Properties and Constructive Aspects of Authenticity: A Reconsideration of Carl Rogers’ Personality Theory - Toper, Aydan (2022)
In the last few decades, there has been a surge of interest in the notion of authenticity as a valid variable of individual differences. While research has demonstrated the variable’s association with well-being, Carl Rogers’ personality approach further suggests that people who are deemed to be more authentic are also more constructive members of society. As there is minimal research to date on the prosocial and pro-environmental aspects of authenticity, the aim of this work is to examine the structural properties of authenticity, as well as the association with more socially and ecologically constructive states of being. The results from the four studies undertaken in this thesis are reported in six chapters. It is shown that there is both a structural similarity and a considerable confluence between the seemingly divergent concepts of authenticity and mindfulness. Authenticity was found to moderate the association between self-compassion and the Kindness, Common Humanity, Mindfulness, and Indifference subscales of the Compassion Scale. It was also found that authenticity has significant and positive association with self-transcendence, a helping attitude and pro-environmental behaviour. Self-transcendence was seen to have a mediating effect on the associations between authenticity and the helping attitudes of altruism, receiving and giving. In addition, authenticity was found to be associated with the humility items of openness, self-forgetfulness and focus on others. It was also seen that there is significantly positive correlation between authenticity, forgiveness, and mindfulness, even when social desirability is partialled out. Furthermore, authenticity partially mediates the association between mindfulness and the two subscales of the Heartland Forgiveness Scale: Forgiveness of Self and Forgiveness of Situations. Measurement of authenticity, performed across two data sets using Exploratory Factor Analysis followed by Confirmatory Factor Analysis, is perhaps best represented by a two-component model which presents a classification between outer and inner expressions of authenticity. The sum of these results advance knowledge of the correlates of authenticity and suggest that authenticity is a quality that is likely to not only benefit the individual, but also others and the environment. Further research that uses more developed methods would therefore be useful to continue the line of enquiry that has been initiated in this study, particularly in terms of the psychometric development of the authenticity construct. This research is necessary to better represent both how the inner and outer manifestations of authenticity are related to each other, and their influence on behaviour.